Origin and provenance of igneous clasts from late Palaeozoic conglomerate formations (Del Ratón and El Planchón) in the Andean Precordillera of San Juan, Argentina - Gallastegui, G.; González-Menéndez, L.; Rubio-Ordóñez, A.; Cuesta, A.; Gerdes, A. (Journal of Iberian Geology, 2014)
Late Palaeozoic conglomerate formations (Del Ratón and El Planchón) from the Andean Precordillera (Argentina) were studied to unravel their age, composition and provenance. The conglomerates from the Del Ratón Formation are formed by igneous clasts of acid, intermediate and basic compositions (volcanic and plutonic). Laser Ablation (ICP-MS) zircon U-Pb study has yielded an age of 348±2 Ma (late Tournaisian) for the crystallization of a granitic clast, interpreted as a maximum deposition age for the Del Ratón Formation. Geochemistry of these clasts (high LILE/HFSE and La/Yb ratios, negative Nb-Ta anomalies) suggests a calc-alkaline batholithic source, probably located along the Andean Frontal Cordillera currently to the west, where similar calc-alkaline igneous rocks have been described. The El Planchón Formation overlies the Del Ratón Formation and, in the studied conglomerates, there are only igneous clasts of mafic composition (volcanic/subvolcanic). These mafic clasts have a very similar petrography and geochemistry to the Late Ordovician mafic igneous rocks of the Western Precordillera (low LILE/HFSE and La/Yb ratios, no negative Nb-Ta anomalies). Therefore we suggest that the El Planchón conglomerate clasts were probably delivered mainly from northern sources within the Precordillera terrane. This change in clast provenance is tentatively related to a shift in mountain uplift from the Frontal Cordillera (in the west) to the Precordillera (in the east) after the early Visean.